Analisis Efektivitas Penggunaan Teknologi Cloud Computing Dalam Peningkatan Bisnis - Telaumbanua, Agus Fortiman (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Cloud computing has grown rapidly in recent years and is being adopted by many companies to improve the efficiency of their businesses. This technology offers various advantages such as reduced infrastructure costs, flexible scalability, better data accessibility, and more effective collaboration capabilities. This journal aims to analyze the effectiveness of using cloud computing technology in improving business efficiency, as well as explore the challenges and benefits faced by companies implementing this technology.